Floristic community composition in Rafflesia's habitat at Kinabalu Park, Sabah - Rasyidah Wahab; Kartini Saibeh; Shamsul Khamis; Handry Mujih; Geofarry Gunsalam; Dasini; Ezron Gerald; Rayzigerson Rodney Chai; Mohd Fadil; Venly; Federica Karolus (Penerbit UMS, 2021)
In the vicinity of Kinabalu Park, Sabah, a study was conducted to determine the plant community and its composition in the habitat of Rafflesia sp. and its host, Tetrastigma sp. A total of 5 circular-shaped plots each with a fixed radius of 20 meters, were located around Kinabalu Park, namely in Losou Podi, Losou Minunsud, Sayap Substation, Langanan and Gansurai. The Rafflesia species detected in Kinabalu Park during the present study were Rafflesia pricei and R. keithii. Overall, 19 Rafflesia individuals were detected, which comprised of 3 flowers and 16 buds. A total of 20 scars from former dead flowers and buds were obtained on the host, where they possessed an average diameter of 2.2-4.8 cm from the five plots. There were 778 individuals recorded for plant community, belonging to 111 genera, 53 families and 250 species. The total tree density was 1238 individuals/ha, where the family Lauraceae (11.05%) had the highest individuals followed by Annonaceae (8.61%). Although the species Baccaurea lanceolata were found in all study plots, the species Xantophyllum macrophyllum has the most individuals detected (3.60%) in the plant community habitats. The value of the Shannon-Wiener Index was H’=3.23 and the Evenness Index is low, E=0.10. The percentage of family similarity between plots was high (SBC=70.19–48.23%), but the percentage of species similarity between plots was very low (SJ=4.31–1.54%). This study shows that both the species of Xanthophyllum macrophyllum and Baccaurea lanceolata have a relationship with the habitat of Rafflesia in Kinabalu Park, as both species were located nearest to the Rafflesia’s host. Moreover, these two species were seen to be well associated with Tetrastigma since the Tetrastigma was observed to climb several trees of these species in the plot.